ISLAMISASI ILMU EKONOMI - IRFAN SAUQI BEIK (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2016)
Abstract. Islamization of Economics. Islamic doctrine teaches all areas of human life. How to extract economic principles in the Qur'an and hadith are the biggest challenge todays, and then makes it into a body of knowledge as well to build it into a theoretically and practically discipline that differ significantly from the schools of the existing the conventional economics. But the critique and issue come up those Islamic financial services only